Exploring clinicians' perspectives on the 'Obstetric Anal Sphincter Injury Care Bundle' national quality improvement programme: a qualitative study. Issue 9 (9th September 2020) - Bidwell, Posy; Thakar, Ranee; Gurol-Urganci, Ipek; Harris, James M; Silverton, Louise; Hellyer, Alexandra; Freeman, Robert; Morris, Edward; Novis, Vivienne; Sevdalis, Nick
Abstract : Introduction: Obstetric anal sphincter injuries (OASI) can have severe debilitating consequences to women and health systems. The OASI Care Bundle quality improvement programme was introduced in 16 maternity units across England, Scotland and Wales (January 2017 to March 2018) to address increasing OASI rates. Objectives: To explore clinicians' (midwives' and obstetricians') perspectives of the OASI Care Bundle with respect to (1) acceptability, (2) feasibility, and (3) sustainability. Design: A qualitative exploratory study using focus groups methodology. Setting: A total of 16 focus groups were conducted in 16 maternity units in England, Scotland and Wales where the OASI Care Bundle was implemented. Focus groups took place approximately 3 months following initial implementation of the care bundle in each unit. Participants: A total of 101 clinicians participated, with an average of six per focus group. Participants volunteered to take part and compromised of 37 obstetricians and 64 midwives (including eight students). The majority were female and the mean age was 36.5 years. Results: Four main themes emerged: 'Implementation strategies', 'Opportunities to use the OASI Care Bundle', 'Does current practice need to change?' and 'Perceptions of what women want'. Midwives were more likely than obstetricians to report themes alluding to 'what women want' and variations in intrapartum perineal protection techniques. Both professional groups reported similar views of other themes, in particular regarding the supporting clinical evidence. Gaps were identified in clinicians' knowledge and experience of intrapartum perineal management. Conclusions: Adoption of the OASI Care Bundle was associated with a number of cognitive and interpersonal factors, such as personal values, interprofessional working and how the intervention was launched; which both facilitated and impeded adoption. The 'what women want' theme has implications for maternal autonomy and needs further exploration. Our findings can be used by similar initiatives to reduce perineal trauma both nationally and internationally. Trial registration number: ISCTRN 12143325; https://doi.org/10.1186/ISRCTN12143325 .